Methane production potentials, pathways, and communities of methanogens in vertical sediment profiles of river Sitka - Mach, Václav; Blaser, Martin B.; Claus, Peter; Chaudhary, Prem P.; Rulík, Martin (Frontiers in Microbiology, 2015)
Biological methanogenesis is linked to permanent water logged systems, e.g. rice field soils or lake sediments. In these systems the methanogenic community as well as the pathway of methane formation are well described. By contrast, the methanogenic potential of river sediments is so far not well investigated. Therefore, we analyzed a) the methanogenic potential (incubation experiments), b) the pathway of methane production (stable carbon isotopes and inhibitor studies), and c) the methanogenic community composition (terminal restriction length polymorphism of mcrA) in depth profiles of sediment cores of River Sitka, Czech Republic. We found two distinct maxima for the methanogenic potentials (a). The pathway of methane production was dominated by hydrogenotrophic methanogenesis (b). The methanogenic community composition was similar in all depth layers (c). The main TRFs were representative for Methanosarcina, Methanosaeta, Methanobacterium and Methanomicrobium species. The isotopic signals of acetate indicated a relative high contribution of chemolithotrophic acetogenesis to the acetate pool.